Distribution and storage of soil organic and inorganic carbon in steppe riparian wetlands under human activity pressure. (June 2022) - Liu, Xinyu; Lu, Xixi; Yu, Ruihong; Sun, Heyang; Li, Xiangwei; Li, Xiang; Qi, Zhen; Liu, Tingxi; Lu, Changwei
Highlights: The SOC storage was primarily affected by vegetation coverage, soil water content, and soil pH, whereas the SIC storage was greatly affected by soil texture. Riparian wetlands were potential hotspots of SOC storage and SIC storage. Human activities have caused carbon storage function weaken and carbon loss accelerated in the riparian wetlands. Abstract: Soil organic carbon (SOC) and soil inorganic carbon (SIC) are key components of the global wetland soil carbon pool, which plays a crucial role in carbon cycling. However, research on carbon storage in riparian wetland soils, especially in inland steppe river environments impacted by human activities, is relatively scarce. Thus, we evaluated the SOC and SIC distributions and storage in riparian wetland soils under the pressure of human activities in the Xilin River Basin (XRB). We collected surface and profile soil samples, determined the SOC and SIC contents, aboveground biomass, and soil physicochemical properties, and calculated the SOC and SIC storage (SOCs and SICs) values. The surface soil SOC content decreased substantially from the upstream to the downstream zones (mean value range: 76.30–3.18 g/kg), and the SIC content showed the opposite trend (mean value range: 0.08–34.38 g/kg). The SIC content of the riparian wetlands along the permanently flowing stretch of river was much lower than that in the wetlands along the intermittently flowing stretch. In the XRB, the SOCs was primarily affected by vegetation coverage, soil water content, and soil pH, whereas the SICs was greatly affected by soil texture. A dry lake zone was markedly affected by wetland degradation, indicating a potential increase in the decomposition rate of the surface soil SOC; however, the SOC in the deep soils was relatively stable. The high SIC content most likely resulted from weathering, resuspension, and carbonate rock reprecipitation. Compared to different steppe grassland types, riparian wetlands appear to be potential hotspots of SOCs and SICs in the Inner Mongolian region. Riparian wetland SOCs in the upstream zones was substantially greater than in adjacent terrestrial locations. However, the SOCs in the downstream wetlands was similar to that in the grasslands. Under the impact of human activities, the water and soil environments in the downstream zone of the Xilin River were substantially modified, leading to severe wetland degradation, which most likely caused the carbon storage function of the riparian wetlands to weaken and carbon loss to accelerate. The mean SOCs in the riparian wetland soils decreased from 33.3 kg/m 2 in the upstream area to 16.2 kg/m 2 downstream, and the mean SICs increased from 2.3 kg/m 2 to 34.6 kg/m 2 . Therefore, urgent measures are needed to restore the carbon sink function of river wetlands for long-term climate change mitigation.